USE OF SCHOOL LIBRARY TO INCREASE STUDENTS' READING INTEREST IN BANYUAJUH 6 ELEMENTARY SCHOOL - Putri Sembada Nani; Agung Setyawan (Citra Dharma Cindekia, 2022)
This study aims to find alternatives to increase students' interest in reading through the library at Banyuajuh 6 Elementary School. The low level of interest in reading can affect the quality of the Indonesian nation itself. Low interest in reading, of course, students will not know and follow the development of science and information in the world. The library is used so that later students can make reading as a hobby. This type of research uses descriptive research with a quantitative approach. This research was conducted by formulating a research problem looking for references from relevant and similar journals to analyze the data, journals were collected by searching the internet through Google Chendikia and/or Google Scholar. Also using data collection techniques using interviews, observation, and documentation. The location of this research was at Banyuajuh 6 elementary school in Kamal sub-district, Bangkalan Regency. Primary data were obtained from teachers, students, and librarians. The results of the study show that efforts to use the school library to increase reading interest at Banyuajuh 6 elementary school have carried out several efforts and can be said to be successful in alleviating low interest in reading at Banyuajuh 6 elementary school.